Penerapan Strategi Customer Relationship Management (CRM) Pada Sistem Informasi Pelayanan Pelanggan Studi Kasus : Rumah Kreatif Ogan Ilir Indralaya - Amatullah, Shabrina; Syafitri, Hidayah; Delima, Rizki; Ibrahim, Ali (Fakultas Ilmu Komputer, Universitas Brawijaya, 2018)
Customer Service Information System that implements Customer Relationship Management (CRM) strategy is a tool used to drive Creative House Ogan Ilir Indralaya so as to improve the quality of service to its customers. The implementation of this CRM strategy uses a web-based system that can manage customer data, product promotions, product sales data and customer service used for customers. The purpose of the implementation of CRM strategy in information systems is to retain existing customers by increasing customer satisfaction to service. The level of user satisfaction will be known from the questionnaire to be used in the Servqual (Quality of Service) method. With the implementation of Customer Relationship Management strategy in customer service information system expected information and services can be more quickly and easily.